2009
DOI: 10.1371/journal.pone.0005614
|View full text |Cite
|
Sign up to set email alerts
|

Body Awareness: Construct and Self-Report Measures

Abstract: ObjectivesHeightened body awareness can be adaptive and maladaptive. Improving body awareness has been suggested as an approach for treating patients with conditions such as chronic pain, obesity and post-traumatic stress disorder. We assessed the psychometric quality of selected self-report measures and examined their items for underlying definitions of the construct.Data sourcesPubMed, PsychINFO, HaPI, Embase, Digital Dissertations Database.Review methodsAbstracts were screened; potentially relevant instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
509
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(535 citation statements)
references
References 151 publications
(171 reference statements)
13
509
0
13
Order By: Relevance
“…This explains the flexion pattern cyclists staying in flexion during cycling, the cricketers leaning over onto the painful side even more towards end-range as well as the rotation group (reporting pain on rotation) doing more rotation than the painfree group. In other words, athletes do not seem to automatically be assuming the best movement pattern and this might be explained by poor body awareness (46) and poor proprioception (47). We need to acknowledge that psychological factors could explain some MCI too (48), and more studies are needed to clarify the issue in athletes with LBP.…”
Section: Discussionmentioning
confidence: 99%
“…This explains the flexion pattern cyclists staying in flexion during cycling, the cricketers leaning over onto the painful side even more towards end-range as well as the rotation group (reporting pain on rotation) doing more rotation than the painfree group. In other words, athletes do not seem to automatically be assuming the best movement pattern and this might be explained by poor body awareness (46) and poor proprioception (47). We need to acknowledge that psychological factors could explain some MCI too (48), and more studies are needed to clarify the issue in athletes with LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Mehling ve ark. [12] artan vücut farkındalığının obezite, posttravmatik stres ve kronik ağrısı olan hastaların hayata uyum sürecini iyi yönde etkilediğini ortaya koymuşlardır. Smith ve ark.…”
Section: Discussionunclassified
“…Yüksek puan vücut duyarlılığının daha iyi olduğunu göstermektedir. [11,12] İstatistiksel analizler için "SPSS for Windows 13.0" paket sürümü kullanıldı. Tanımlayıcı yöntemlerin yanı sıra Pearson korelasyon analizi kullanıldı.…”
Section: Değerlendirme öLçekleriunclassified
“…The complete version of the questionnaire includes five subscales related to stress and perception of bodily responses. The awareness subscale of the BPQ however has in past studies been demonstrated to be a useful measure of self-rated bodily awareness (Critchley et al, 2004;Mehling et al, 2009), and was here used to assess possible differences in interoceptive awareness between participants.…”
Section: Awareness Sub-scale Of Body Perception Questionnaire (Bpq)mentioning
confidence: 99%